Epidemiological characteristics and spatial clustering analysis of human brucellosis in Zibo City, Shandong Province, China, 2006–2024 - Rongtao Zhao; Ruixuan Sun; Feng Zhang (Frontiers in Public Health, 2025)
BackgroundThe significant rise in human brucellosis incidence is a serious public health issue in Zibo City. However, its temporal and spatial distribution has not been thoroughly investigated.ObjectiveThis study aims to describe the demographic, temporal, and spatial distribution patterns and clustering characteristics of human brucellosis cases in Zibo City from 2006 to 2024, in order to develop and implement effective scientific prevention and control strategies.MethodsCase data were obtained from the Infectious Disease Surveillance System of the Chinese Disease Control and Prevention Information System. The epidemiological characteristics and spatial aggregation of human brucellosis were analyzed using descriptive analysis and spatial autocorrelation analysis. The incidence of brucellosis in 2025 was predicted using an ARIMA model.ResultsData on human brucellosis cases in Zibo City from 2006 to 2024 were obtained from the national infectious disease reporting information management system. Spatial autocorrelation analysis and temporal-spatial scan statistics were used to identify potential changes in the temporal-spatial distribution of human brucellosis in Zibo City. From 2006 to 2021, a total of 2,176 brucellosis cases were reported in Zibo City, with an average annual incidence rate of 2.50 per 100,000. Middle-aged and older adult populations (aged 35–74 years) were the primary affected groups, accounting for 86.76% (1,888/2,176) of all reported cases. The incidence of brucellosis in Zibo City showed a long-term upward trend and exhibited significant seasonal variations, with peaks occurring between March and September each year. From 2006 to 2024, the incidence gradually expanded from the northern and central regions to the southern regions. Global spatial autocorrelation analysis revealed a positive correlation in brucellosis incidence between 2009 and 2012–2024. Spatiotemporal cluster analysis identified a primary cluster in the high-incidence areas of northern Zibo City, with four secondary clusters appearing in areas where brucellosis outbreaks had previously occurred. According to ARIMA model predictions, the monthly incidence rate of brucellosis in Zibo City has declined steadily from 0.75/100,000 in 2010 to near-zero levels by 2020 and is projected to remain extremely low through 2025.ConclusionHuman brucellosis remains a serious public health concern in Zibo City. Special monitoring and control plans and measures may be required for the high-incidence areas in northern Zibo. Additionally, epidemic response capabilities should be enhanced in high-incidence areas to prevent further increases in brucellosis incidence.